Essential Oil from Inula britannica Extraction with SF-CO2 and Its Antifungal Activity - Te ZHAO; Fei GAO; Lin ZHOU; Tian-you SONG (Journal of Integrative Agriculture)
The aim of this study was to determine the extraction technique of supercritical fluid carbon dioxide (SF-CO2) for the essential oil from Inula britannica flowers and its antifungal activities against plant pathogenic fungi for its potential application as botanical fungicide. The effects of factors, including extraction temperature, extraction pressure, SF-CO2 flow rate, flower powder size, and time on the essential oil yield were studied using the single factor experiment. An orthogonal experiment was conducted to determine the best operating conditions for the maximum extraction oil yield. Adopting the optimum conditions, the maximum yield reached 10.01% at 40°C temperature, 30 MPa pressure, 60 mesh flower powder size, 20 L h−1 SF-CO2 flow rate, and 90 min extraction time. The antifungal activities of I. britannica essential oil using the SF-CO2 against the most important plant pathogenic fungi were also examined through in vitro and in vivo tests. Sixteen plant pathogenic fungi were inhibited to varying degrees at 1 mg mL−1 concentration of the essential oil. The mycelial growth of Gaeumannomyces graminis var. tritici was completely inhibited. The radial growths of Phytophthora capsici and Fusarium monilifome were also inhibited by 83.76 and 64.69%, respectively. In addition, the essential oil can inhibit the spore germination of Fusarium oxysporum f. sp. Vasinfectum, Phytophthora capsici, Colletotrichum orbiculare, and Pyricularia grisea, and the corresponding inhibition rates were 98.26, 96.54, 87.89, and 87.35% respectively. The present study has demonstrated that the essential oil of I. britannica flowers extracted through the SF-CO2 technique is one potential and promising antifungal agent that can be used as botanical fungicide to protect crops.